Possibility of reducing water hardness with biochar derived from waste biomass (Bulletin of the Institute of Chemistry and Chemical Technology, 2022)
By heating waste biomass in an oxygen-deficient environment (pyrolysis), biochar is produced, which is a carbon-like combustion product with a porous structure, alkaline properties, and a large surface area. Research on the absorption of heavy metals, drug residues, dyes, and fluoride ions from the aquatic environment using biochar has been conducted in other countries of the world, but limited experiments have been conducted to reduce the major ions that compose water hardness. This research aims to investigate the possibility of reducing water hardness using biochar derived from animal waste bones and dung. Sheep waste bonesand cow dung were pyrolyzed in a TLUD furnace at a temperature of 500-550°C for 1-2 hours to obtain appropriate biochar. To reduce the content of calcium, magnesium, and hydrocarbonate ions, which compose water hardness, the biochar obtained was used as adsorbent material in series (batch) experiments in synthetic (artificially mineralized) water and natural (well) water, respectively. The optimal conditions for the adsorption process were determined with the type of primary raw materials, the mixing amount (dosage) of biochar with water, and the time of adsorption. Bone char adsorbed water hardness better than dung char, and the adsorption capacity was higher when the initial ion concentration of ions was higher. As a result of the adsorption test, taking into account the content of calcium, magnesium and hydrogen carbonate ions, 38%; 19%; was reduced by 34%, while total water hardness was reduced by an average of 22%. Biochar derived from animal waste bones can reduce water hardness by adsorbing the major ionsХаягдал биомассаас гарган авсан бионүүрсээр усны хатуулгийг бууруулах боломжХураангуй: Хаягдал биомассыг хүчилтөрөгч дутмаг орчинд халаах (пиролиз) замаар нүх сүвэрхэг бүтэцтэй, шүлтлэг шинж чанартай, гадаргуугийн талбай ихтэй нүүрс төст шаталтын бүтээгдэхүүн болох бионүүрсийг гарган авдаг. Бионүүрс ашиглан усан орчноос төрөл бүрийн хүнд металл, эмийн үлдэгдэл бодис, будагч бодис, фторид ион зэргийг шингээдэг судалгаа дэлхийн бусад орнуудад нэлээд хийгдсэн боловч усны гол катион, анионуудыг бууруулах туршилт төдийлөн олон хийгдээгүй байна. Энэхүү судалгааны ажлаар малын яс, аргалаас гарган авсан бионүүрсийг ашиглан усны хатуулгийг бууруулах боломжийг судлахыг зорилоо. Хонины хаягдал яс, үхрийн аргалыг TLUD-ын зуухан дотор 500-550°C-ийн температурт 1-2 цагийн турш пиролизод оруулж зохих бионүүрсийг гарган авсан. Гарган авсан бионүүрсээ шингээгч материал болгон ашиглаж, усны хатуулгийг бүрдүүлэгч кальци, магни, гидрокарбонат ионуудын агуулгыг бууруулах цуврал (batch) туршилтыг зохиомол эрдэсжилттэй ус болон байгалийн усанд тус тус хийж гүйцэтгэсэн. Шингээлтэд бионүүрсний анхдагч түүхий эд, бионүүрсийг усанд холих хэмжээ (тун), шингээлт явуулах хугацаа хэрхэн нөлөөлж буйг туршин шингээлтийн процессын зохист нөхцөлийг тодорхойлсон. Ясны бионүүрс аргалын бионүүрснээс илүүтэйгээр усны хатуулгийг сайн шингээж байсан бөгөөд анхны ионы концентрац өндөр байхад адсорбцын багтаамж өндөр байсан. Адсорбцын туршилтын үр дүнд кальци, магни, гидрокарбонат ионуудын агуулгыг харгалзан 38%; 19%; 34%-иар бууруулж байсан бол усны нийт хатуулгийн хэмжээг дунджаар 22%-иар бууруулж байсан. Малын хаягдал яснаас гарган авсан бионүүрс нь усны хатуулгийг бүрдүүлэгч гол ионуудыг өөртөө шингээж, хатуулгийн хэмжээг бууруулах бүрэн боломжтой.Түлхүүр үг: малын яс, аргал, шингээгч материал, усны эрдэсжилт, усны чанар